2021
DOI: 10.1038/s43246-021-00121-6
|View full text |Cite
|
Sign up to set email alerts
|

Piezomagnetic switching and complex phase equilibria in uranium dioxide

Abstract: Actinide materials exhibit strong spin–lattice coupling and electronic correlations, and are predicted to host new emerging ground states. One example is piezomagnetism and magneto-elastic memory effect in the antiferromagnetic Mott-Hubbard insulator uranium dioxide, though its microscopic nature is under debate. Here, we report X-ray diffraction studies of oriented uranium dioxide crystals under strong pulsed magnetic fields. In the antiferromagnetic state a [888] Bragg diffraction peak follows the bulk magne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 27 publications
1
6
0
Order By: Relevance
“…Elastic constants have been studied experimentally using a pulse-echo technique on single crystals of ThO 2 and UO 2 at room temperature. , The thermal expansion of UO 2 single crystals was measured by Brandt and Walker in 1967. , That was the first direct demonstration that the phase transition is first-order in the lattice properties. The volume collapse at T N was first observed in 1974 and, more recently, by X-ray diffraction . Furthermore, the measurements of elastic constants versus temperature have not only exhibited changes at the magnetic transition but also confirmed that the elastic properties at high temperature (up to room temperature) are much more complicated than anticipated.…”
Section: Thermal Transport In Perfect Single Crystalssupporting
confidence: 73%
See 2 more Smart Citations
“…Elastic constants have been studied experimentally using a pulse-echo technique on single crystals of ThO 2 and UO 2 at room temperature. , The thermal expansion of UO 2 single crystals was measured by Brandt and Walker in 1967. , That was the first direct demonstration that the phase transition is first-order in the lattice properties. The volume collapse at T N was first observed in 1974 and, more recently, by X-ray diffraction . Furthermore, the measurements of elastic constants versus temperature have not only exhibited changes at the magnetic transition but also confirmed that the elastic properties at high temperature (up to room temperature) are much more complicated than anticipated.…”
Section: Thermal Transport In Perfect Single Crystalssupporting
confidence: 73%
“…That was the first direct demonstration that the phase transition is first-order in the lattice properties. The volume collapse at TN was first observed in 1974 [190] and, more recently, by X-ray diffraction [191]. Furthermore, the measurements of elastic constants versus temperature have not only exhibited changes at the magnetic transition but also confirmed that the elastic properties at high temperature (up to room temperature) are much more complicated than anticipated.…”
Section: Elastic Constants and Thermal Expansionmentioning
confidence: 60%
See 1 more Smart Citation
“…A number of experiments using pulsed magnetic fields have been performed with SR, e.g., (Detlefs et al, 2008b), but the first one on an actinide system, was reported from the APS on UO 2 (Antonio et al, 2021). The results are shown in Fig.…”
Section: Experiments At High Magnetic Fieldsmentioning
confidence: 99%
“…A recent X-ray study on UO 2 single crystals evidences the presence of AFM domains and subsequently the coexistence of AFM phases L 0 and −L 0 connected by timereversal even in magnetic fields beyond the piezomagnetic switching field [22]. This is also supported by magnetostriction measurements [2], which show that the first pulse taken below T N always has a smaller magnetostriction slope for fields below the switching field.…”
Section: Discussionmentioning
confidence: 71%